Ulomki v vrtcu - Lipovec, Alenka; Antolin, Darja; Vaupotič, Alenka (Revija za elementarno izobraževanje, 2012)
Fractions in kindergarten. This article presents the initial concepts of understanding rational numbers in kindergarten, and the introduction of fractions in kindergarten. Based on relevant literature, we have established that the development of early concepts of fractions is reasonable in the pre-school period already, although the Slovenian kindergarten curriculum does not foresee it. We have prepared some contextualized tasks involving geometric and measurable model of fractions, which have already proven effective elsewhere. For the purpose of research, children were asked to solve those tasks individually with the support of adults. The research involved preschool children at the age of five. We were interested to discover the differences in solving fractions tasks between children who had previous experience with fractions and those who first came into contact with this content on the day of the retention test, that is, a month later. The information we obtained through observation sheets have shown that children who were already familiar with the content solved the test tasks without major difficulties. Thus, the children in the experimental group performed better in their final examination than the children in the control group, who were confronted with fractions for the first time. However, the children in the control group also demonstrated sufficient knowledge, so we can conclude that the tasks prepared were appropriate with regard to their developmental stage.